Rapid infancy weight gain during the complementary feeding period in a cohort of Spanish infants. Issue 1 (1st January 2019) - Iguacel, Isabel; Álvarez, Lino; Cabero, Mª Jesús; Monje, Laura; Moreno, Luis A.; Rodriguez-Palmero, María; Rivero, Montserrat; Samper, Pilar; Rodríguez, Gerardo
ABSTRACT: Objectives : The relation between rapid infancy weight gain (RWG) and childhood obesity has been extensively evaluated but studies examining total food intake and food groups among infants with RWG and normal weight gain (NWG) are limited. Therefore, we aimed to explore: (i) the characteristics of infants with a rapid growth during the second semester of life; (ii) the association between feeding practices (breast-fed vs. formula-fed infants) and RWG and (iii) the association between food intake and food patterns at 9 months of age and RWG. Study design : One-year follow-up study of a cohort of infants from the north of Spain. Methods : 195 infants were measured. Parents recorded all infant´s food consumption for 3 days (grams/day). Mixed-effects logistic regression models were applied. Results : In basic models, breast-feeding practices were associated with a lower risk of RWG (OR = 0.54, 95%CI 0.35–0.84) compared to formula-fed infants. However, this association was no longer significant when additionally adjusting for early-life risk factors and total food intake. Infants with RWG had a higher intake of cereals (OR = 1.03, 95%CI 1.00–1.07), fruit baby food (OR = 1.01, 95%CI 1.00–1.01), and total food intake (OR = 1.02, 95%CI 1.00–1.04) at 9 months of age. Conclusions : Infants with rapid growth during the second semester of life had a higher intake of cereals, fruit baby food, and total food intake compared to the NWG group. Differences in food patterns and intake among infants with rapid weight gain during the second semester might lead to programming towards childhood obesity.